Tennis and learning through the Fit Junior Program: Observations and results for the didactics aim - Santopietro, F.; Fattore, S.; Di Domenico, F.; Sannicandro, I. (Journal of Human Sport & Exercise, 2020)
For some years, the Italian Tennis Federation has made use of the national didactic evaluation and learning quality certification system of the Fit Junior Program, geared at accompanying young students on an introductory path consisting of a series of steps, with the aim of dividing learning into goals. With respect to this program, the aim of this study is to observe the learning of tennis within a group of "Dolphin level" beginner children, of the Potenza Tennis Club. Attention was focused on the evaluation of five technical aspects: strikes with feet planted firmly on the ground; strikes by swinging the racket forward; also uses the non-dominant limb; shifts body weight from back to front; and strikes the ball at the right time. Each of them has been assigned a value between 1 (poor skill) and 5 (excellent skill), based on the skills acquired by the child during the five months of observation. The children underwent an evaluation both before and after the training period. Through the use of the Pearson correlation, it can be said that the working method carried out has made it possible to achieve positive results, confirming the effectiveness and validity of the Fit Junior Program.